1989
DOI: 10.1111/j.1365-2141.1989.tb00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistology for Quantification of Normal Bone Marrow Lymphocyte Subsets

Abstract: Dokal et a1 (1 989), and maybe also as a result of the previous splenectomy, we observed a prompt engraftment in spite of the myelofibrosis, which might have adversely affected posttransplant haematopoietic reconstitution (Rajantie et al, 1986). We agree with these authors that BMT should be considered as treatment of choice for young patients with primary myelofibrosis, especially when poor prognosis features are present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 6 publications
4
9
0
Order By: Relevance
“…In the present study, however, the T and the B subsets were present in equivalent percentages in adults, in agreement with the results obtained in B-5 fixed decalcified BM biopsies reported by O'Donnel et al (32). However, the percentages of lymphoid subsets reported by immunohistochemical studies (21,32,39) are relative to total nucleated cells in BM or to the analyzed area (32), and comparison with those results obtained by flow cytometry is inaccurate. Considering only the previous studies of BM by flow cytometry, our results showed higher percentages of both T and B cells, even compared with data obtained from biopsies (9).…”
Section: Discussionsupporting
confidence: 61%
“…In the present study, however, the T and the B subsets were present in equivalent percentages in adults, in agreement with the results obtained in B-5 fixed decalcified BM biopsies reported by O'Donnel et al (32). However, the percentages of lymphoid subsets reported by immunohistochemical studies (21,32,39) are relative to total nucleated cells in BM or to the analyzed area (32), and comparison with those results obtained by flow cytometry is inaccurate. Considering only the previous studies of BM by flow cytometry, our results showed higher percentages of both T and B cells, even compared with data obtained from biopsies (9).…”
Section: Discussionsupporting
confidence: 61%
“…A putative positive staining of a few histiocytic cells was recognized during morphometric evaluation of the bone marrow samples, but not regarded in our calculations. In confirmation and extension to previous findings (14,33), morphometric quantification on paraffin sections derived from our control group of patients showed a similar ratio (4:1) between CD45RO ϩ and CD20 ϩ lymphocytes in hematopoietic tissue (Table 2). On the other hand, a more comprehensively conducted comparison between normal and CML bone marrow specimens has to regard cellularity (i.e., the amount of hematopoiesis).…”
Section: Discussionsupporting
confidence: 91%
“…First of all, a conflict of opinion still persists regarding the exact number or ratio of T-and B-lymphocytes in the normal bone marrow. According to immunohistologic analysis of bone marrow frozen sections, the ratio is about 9% T-lymphocytes (2.7% CD4 ϩ and 6.3% CD8 ϩ ) to 1.5% (CD22 ϩ ) B-lymphocytes (33). This T-to B-cell ratio is generally comparable with the CD45R0-and CD20-reactivity of lymphocyte subsets in paraffin-embedded bone marrow trephine biopsies amounting between 4:1 and 5:1 (14).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…These studies relied on BM donations from sibling donors, including a few children, or on trephine biopsies obtained during surgery or from volunteers. A major finding was that BM contains increased numbers of CD8+ T cells compared to peripheral blood, resulting in lower CD4/CD8 cell ratios [25,27,28,29]. Among BM lymphocytes upon diagnosis of ALL, we found highly variable CD4/CD8 ratios with a median of 1.22, slightly above that reported for normal BM.…”
Section: Discussionmentioning
confidence: 73%